The effect of COVID-19 vaccine to the Omicron variant in children and adolescents: a systematic review and meta-analysis - Lu, Wenting; Zeng, Shuai; Yao, Yuan; Luo, Yiting; Ruan, Tiechao (Frontiers in Public Health, 2024)
Background: Omicron (B.1.1.529), a variant of SARS-CoV-2, has emerged as a dominant strain in COVID-19 pandemic. This development has raised concerns about the effectiveness of vaccination to Omicron, particularly in the context of children and adolescents. Our study evaluated the efficacy of different COVID-19 vaccination regimens in children and adolescents during the Omicron epidemic phase. Methods: We searched PubMed, Cochrane, Web of Science, and Embase electronic databases for studies published through March 2023 on the association between COVID-19 vaccination and vaccine effectiveness (VE) against SARS-CoV-2 infection in children and adolescents at the Omicron variant period. The effectiveness outcomes included mild COVID-19 and severe COVID-19. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was prospectively registered in PROSPERO (CRD42023390481). Results: A total of 33 studies involving 16,532,536 children were included in the analysis. First, in children and adolescents aged 0-19 years, the overall VE of the COVID-19 vaccine is 45% (95% confidence interval [CI]: 40% to 50%). Subgroup analysis of VE during Omicron epidemic phase for different dosage regimens demonstrated that the VE was 50% (95% CI: 44% to 55%) for the 2-dose vaccination and 61% (95% CI: 45% to 73%) for the booster vaccination. Upon further analysis of different effectiveness outcomes during the 2-dose vaccination showed that the VE was 41% (95% CI: 35% to 47%) against mild COVID-19 and 71% (95% CI: 60% to 79%) against severe COVID-19. In addition, VE exhibited a gradual decrease over time, with the significant decline in the efficacy of Omicron for infection before and after 90 days following the 2-dose vaccination, registering 54% (95% CI: 48% to 59%) and 34% (95% CI: 21% to 56%), respectively. Conclusions: During the Omicron variant epidemic, the vaccine provided protection against SARS-CoV-2 infection in children and adolescents aged 0-19 years. Two doses of vaccination can provide effective protection severe COVID-19, with booster vaccination additionally enhancing VE.